2018
DOI: 10.1002/bip.23088
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic insights into the self‐assembly of KLVFF amyloid‐beta peptides

Abstract: Amyloidogenic peptide fragment KLVFF (H N-Lys-Leu-Val-Phe-Phe-COOH, Aβ ), the core-sequence of the polypeptide Aβ40, is a well-studied model for amyloid formation. However, due to its low crystallinity, detailed atomic information of KLVFF structure is lacking. Here we report the high-resolution single-crystal X-ray structure of two monohalogenated KLVFF derivatives, KLVFF(I) and KLVFF(Br). The obtained results highlight how halogenation is a good strategy to promote crystallization and facilitate the phase de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 50 publications
(62 reference statements)
0
29
0
Order By: Relevance
“…The second is a peptide having a single iodine atom on the aromatic residue at the N‐terminus—F(I)F—(Figure ). Mono‐iodination on the C‐terminus—FF(I)—was not studied, since halogenation in this position was proved to do not have an active role in the self‐assembly, as demonstrated by the crystal structure of KLVFF(I) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second is a peptide having a single iodine atom on the aromatic residue at the N‐terminus—F(I)F—(Figure ). Mono‐iodination on the C‐terminus—FF(I)—was not studied, since halogenation in this position was proved to do not have an active role in the self‐assembly, as demonstrated by the crystal structure of KLVFF(I) …”
Section: Resultsmentioning
confidence: 99%
“…Recent works from our group reported the impact of halogenation in the self‐assembly properties of simple organic systems containing phenylalanine residues. Studies based both on a single phenylalanine and short peptide sequences confirmed that halogenation enhances the self‐aggregating propensity compared to the corresponding nonhalogenated systems, this proclivity being a function of halogen polarizability. Moreover, in the case of amyloid peptide fragments, several kinds of nanostructures were observed by changing number, position, and nature of the halogen substitution .…”
Section: Introductionmentioning
confidence: 87%
“…This problem can be resolved better by nanomedicines staying in shape one, such as spheres, to circulate and distribute in the body, and transforming into another shape, such as fibers, to facilitate the retention inside tumor. Phe‐Phe‐Val‐Leu‐Lys (FFVLK) peptide, derived from β‐amyloid, tends to form a β‐sheet structure relying on extensive intermolecular hydrogen bonds that enable fibers formation . However, after introducing hydrophobic heads and hydrophilic tail in FFVLK peptide, the resultant linear chimeric molecules form micelles when rapidly dissolved in aqueous solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Halogenation of the C-terminus was not included as it was previously shown not to affect the self-assembly of the parent amyloid sequence Lys-Leu-Val-Phe-Phe. 30 Iodination in the ortho- or meta-positions of Phe was not studied as it was envisaged to likely disrupt assembly due to iodine’s bulky nature and ability to engage in halogen bonding with carbonyl groups. 30 Our choice of heterochiral sequences was dictated by the observation that introducing d -amino acids at selected positions has proven successful as a strategy to achieve hydrogels from uncapped tripeptides.…”
mentioning
confidence: 99%